2003
DOI: 10.1124/dmd.31.9.1093
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Studies on the Cytochrome P450-Associated Metabolism and Interaction Potential of Selegiline Between Human Liver-Derived in Vitro Systems

Abstract: This article is available online at http://dmd.aspetjournals.org ABSTRACT:Selegiline was used as a model compound in a project aimed at comparing, evaluating, and integrating different in vitro approaches for the prediction of cytochrome P450 (P450)-catalyzed hepatic drug metabolism in humans (EUROCYP). Metabolic predictions were generated using homology modeling, cDNA-expressed P450 enzymes, human liver microsomes, primary cultured human hepatocytes, and precision-cut human liver slices. All of the in vitro s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
43
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 61 publications
(45 citation statements)
references
References 53 publications
1
43
1
Order By: Relevance
“…Moreover, similarly to what has been observed in mouse, CYPdependent metabolism of PF9601N by human liver microsomes gave rise to a linear EadieHofstee plot suggesting the involvement of only one isozyme, with Km and Vmax values very close to the values observed in the mouse (Table 2). In contrast, the apparent Km values detected with l-deprenyl in mouse were quite different from the values given by human liver microsomes (35)(36). This suggests that the use of mouse liver microsomes to predict l-deprenyl metabolism in humans is inconsistent.…”
Section: Discussioncontrasting
confidence: 47%
“…Moreover, similarly to what has been observed in mouse, CYPdependent metabolism of PF9601N by human liver microsomes gave rise to a linear EadieHofstee plot suggesting the involvement of only one isozyme, with Km and Vmax values very close to the values observed in the mouse (Table 2). In contrast, the apparent Km values detected with l-deprenyl in mouse were quite different from the values given by human liver microsomes (35)(36). This suggests that the use of mouse liver microsomes to predict l-deprenyl metabolism in humans is inconsistent.…”
Section: Discussioncontrasting
confidence: 47%
“…See also articles of Andersson et al (2001); Pelkonen et al (2001) and Salonen et al (2003). the entity.…”
Section: )mentioning
confidence: 99%
“…In contrast, it has been reported that CYP2D6 and CYP2C19 make no major contribution to this reaction (van Agtmael et al, 1998), and the role of other P450s remains unclear. CYP2B6 plays a major role in the biotransformation of several therapeutically important drugs, including cyclophosph-amide, bupropion, selegiline, efavirenz, nevirapine, and methadone (Roy et al, 1999;Hesse et al, 2000;Hidestrand et al, 2001;Salonen et al, 2003). Many genetic polymorphisms in the CYP2B6 gene have been reported, and these are thought to be responsible for interindividual and interethnic differences in responses to CYP2B6 substrate drugs [Zanger et al, 2007; Human Cytochrome P450 (CYP) Allele Nomenclature Committee, 2008;Mo et al, 2009].…”
Section: Introductionmentioning
confidence: 99%